Evaluating speeds of weaving sections at u-turn slots in Metro Manila using HCM 2000. - Galiza, Ronald John
The closure of signalized intersections and the rerouting of traffic into midblock U-turn median openings (U-turns) paved the way for free flow traffic conditions (uninterrupted flow) in an intersection. However, direct left turn vehicles will now have to take a series of right turn plus U-turn (RTUT)maneuvers in order to duplicate the same path taken prior to the closure. As a consequence, RTUT vehicles must lane change across into the innermost lane towards the U-turn slot, thus creating weaving areas. Currently, methods for analyzing the speeds in the weaving segment were derived exclusively on freeway weaving sections. The weaving maneuver that closely compares to the weaving of a RTUT vehicle is the two sided Type C freeway weave. The HCM Weaving Model for Type C was used to speeds were poorly predicted.
Keywords: Arterial weaving speed; U-turn.; Models; Estimation